DAMPAK GAYA KEPEMIMPINAN ADAPTIF, KECERDASAN EMOSIONAL, DAN BUDAYA ORGANISASI TERHADAP KETERLIBATAN KARYAWAN PT HASTARI JAYA SENTOSA - Firnanda, Senis Novi; Saptaria, Lina; Dewi, Anita Sumelvi (Arthavidya Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the influence of adaptive leadership, emotional intelligence, and organizational culture on the level of employee engagement at PT Hastari Jaya Sentosa partially and simultaneously. The approach used is quantitative with descriptive methods. Data were collected through distributing questionnaires to 45 company employees and processed using SPSS software version 25. Data analysis techniques applied include Classical Assumption Test, Multiple Linear Regression Analysis, and Coefficient of Determination Test (R²). The results of the study indicate that adaptive leadership style (X1), emotional intelligence (X2), and organizational culture (X3), partially and simultaneously have a significant influence on employee engagement. The implications of these findings emphasize that organizations need to invest in adaptive leadership training and development, improving emotional intelligence, and strengthening organizational culture holistically to encourage employee engagement.